A dynamic supramolecular polyurethane network whose mechanical properties are kinetically controlled. (20th December 2017) - Tang, Xuegang; Feula, Antonio; Baker, Benjamin C.; Melia, Kelly; Hermida Merino, Daniel; Hamley, Ian W.; Buckley, C. Paul; Hayes, Wayne; Siviour, Clive R.
Abstract: We report the synthesis and characterization of a kinetically controlled, thermoreversible supramolecular polyurethane whose mechanical properties depend unusually strongly on the processing history. Materials were prepared by solution casting, quenching and annealing of quenched material, allowing pronounced micro-structural evolution, which leads to rapid increases in modulus as determined by rheological analysis. Tensile tests showed that the quenched material is soft, weak and ductile (shear modulus ∼ 5 MPa, elongation ∼ 250%), but after annealing, at 70 °C for 1 h, it becomes stiffer, stronger and more brittle (∼20 MPa, ∼20%). FTIR and NMR spectroscopic analysis, coupled with MDSC and SAXS, were performed to investigate the network's dynamic structural changes. SAXS results suggest the presence of a lamellar structure in the sample when solution cast at high temperature, or annealed. This ordering is unique when compared to structurally-related supramolecular bisurethane and bisurea polymers, and may be the cause of the observed path dependence. These mechanical properties, which can be switched repeatedly by simple thermal treatments, coupled with its adhesion properties as determined from peel and tack tests, make it an excellent candidate as a recyclable material for adhesives and coatings. Graphical abstract: Highlights: A novel supramolecular polyurethane forms a kinetically controlled thermoreversible network. Characterisation of structural and mechanical properties following different heat treatments. The mechanical response can be modified over an unusually wide range through thermal treatments. Use of the polymer as an adhesive is explored via peel and tack tests.